Development of Android-Based Learning Media: a Literature Review - Darwin, David; Rafli, Zainal; Setiadi, Samsi (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
The development of information and communication technology such as android has not been widely used to support the learning process. Supposedly technological advances such as android can be utilized in the learning process. This study aims to discover some of the inventions of Android-based learning media that are currently being developed to support an efficient and effective learning process. The research design was in the form of a review of journals published in the Sinta database with the keywords